Deciphering New Players in the Neurogenic Adult Hippocampal Niche - Antonela Bonafina; Gustavo Paratcha; Fernanda Ledda (Frontiers in Cell and Developmental Biology, 2020)
In the mammalian adult hippocampus, new neurons are continuously generated throughout life in the subgranular zone of the dentate gyrus. Increasing evidence point out the contribution of adult-born hippocampal granule cells (GCs) to cognitive processes such as learning and memory, indicating the relevance of understanding the molecular mechanisms that control the development of these new neurons in the preexisting hippocampal circuits. Cell proliferation and functional integration of adult-born GCs is a process highly regulated by different intrinsic and extrinsic factors. In this review, we discuss recent advances related with cellular components and extrinsic signals of the hippocampal neurogenic niche that support and modulate neurogenesis under physiological conditions.